Generalized Quantifiers
VIII, 309 p.
Keywords: Some fifteen years ago, research on generalized quantifiers was con sidered to be a branch of mathematical logic, mainly carried out by mathematicians. Since then an increasing number of linguists and philosophers have become interested in exploring the relevance of general quantifiers for natural language as shown by the bibliography compiled for this volume. To a large extent, the new research has been inspired by Jon Barwise and Robin Cooper's path-breaking article "Generalized Quantifiers and Natural Language" from 1981. A concrete sign of this development was the workshop on this topic at Lund University, May 9-11, 1985, which was organized by Robin Cooper, Elisabet Engdahl, and the present editor. All except two of the papers in this volume derive from that workshop. Jon Barwise's paper in the volume is different from the one he presented in connection with the workshop. Mats Rooth's contribution has been added because of its close relationship with the rest of the papers. The articles have been revised for publication here and the authors have commented on each other's contributions in order to integrate the collection. The organizers of the workshop gratefully acknowledge support from the Department of Linguistics, the Department of Philosophy and the Faculty of Humanities at Lund University, the Royal Swedish Academy of Sciences (through the Wallenberg Foundation), the Swedish Institute, and the Letterstedt Foundation.